Transformasi Stadion Olah Raga KONI di Kawasan Perdagangan Kota Jambi - Setyawan, Denny Iwan (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2023)
KONI Stadium is in the middle of the commercial area, adjacent to the old city center of Jambi. As part of the city's strategic economic area, this area is facing the problems of the decline of the city center, underdeveloped land, underutilized property, minor used only property and the existence of a stadium which is still needed by residents as a sports facility and social space. There are also pockets of old settlements that still survive. So the problem is how to meet these various demands in the stadium area which has become the identity of this region. Furthermore, how can the stadium be transformed functionally to meet new programmatic needs in terms of existing regional problems. To be answered through a qualitative descriptive study by looking at the current morphology of the area and the projected potential for the development of the KONI Stadium area in the future. Literature review was conducted to obtain a theoretical basis that can be used. It is also supported by precedent studies on similar issues. From the study, conclusions were formulated on an urban architectural design model that could meet and answer problems. The mixed-use area design approach is considered capable of meeting a variety of demands and functions. Also proposed a solution related to the transformation of existing settlements in the area. Architecturally, it is designed to be in harmony with the economic value of the land by a vertical building design but provides a gradation of scale that gives respect to the scale of the surrounding residential area and of course to the social humanism aspect which still provides communal space for the existing community with development opportunities. It also provides solutions to environmental problems.